The Use of Crossword Puzzle to Increase Students’ Spelling Ability at SMPN 1 Tamalatea - Anjelina, Lusy; Muliati, A.; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research aimed to determine whether or not the use of crossword puzzle can increase the students’ spelling ability. This research used a quantitative approach with a pre-experimental design. The population of this research was the grade VIII students of SMPN 1 TAMALATEA by using cluster random sampling with a population of 6 classes and the selected sample was grade 8.1 which amounted to 26 students. The data were collected through spelling tests carried out during the pre-test and post-test. The data were analyzed using t-test statistics with a significance value of 0.05. The results of the data analysis show a probability value (sig. 2-tailed) of 0.000 is smaller than the significance value of 0.05. Therefore, this research rejects the null hypothesis (H0) and accepts the alternative hypothesis (H1). Based on these results, the researcher concludes that the use of crossword puzzle can increase students’ spelling ability at SMPN 1 TAMALATEA.